Guanine chemiluminescent biosensor capable of rapidly sensing mercury in a sample. Issue 115 (3rd November 2015) - Kwon, M.; Park, Y.; Lee, J. H.
Abstract : Using DNA aptamer (T–Hg 2+ –T hairpin-DNA) and guanine chemiluminescene detection, a highly sensitive biosensor was developed for the rapid quantification and monitoring of Hg 2+ in drinking water. Abstract : Using DNA aptamer and guanine chemiluminescene detection, we developed a highly sensitive biosensor for the rapid quantification and monitoring of Hg 2+ in drinking water. The random coil structure of DNA aptamer was transformed to a hairpin-link thymine (T)–Hg 2+ –T complex, closed by the hybridization of guanine and cytosine of DNA aptamer, in the presence of Hg 2+ in drinking water. The brightness of light, emitted from the reaction between guanine of the DNA aptamer and 3, 4, 5-trimethoxyl phenylglyoxal hydrate (TMPG) in the presence of tetra- n -propylammonium hydroxide (TPA) and O2, exponentially decreased with the increase of Hg 2+ due to the transformation of DNA aptamer. The sensitivity of the biosensor was dependent on the incubation time for forming the hairpin-link T–Hg 2+ –T complex closed by the hybridization of guanine and cytosine of the DNA aptamer. The sensitivity of the biosensor was the highest when DNA aptamer was incubated with Hg 2+ for 20 min at room temperature (21 ± 2 °C). The sensitivity of the biosensor generated with incubation longer than 20 min was not as good as that operated with a 20 min incubation because the dehybridization of guanine and cytosine of DNA aptamer is predominant after 20 min. The limit of detection (LOD = CL0 − 3 σ ) of the biosensor operated with a 20 minute incubation was as low as 2.11 nM. Also, the accuracy, precision, and recovery of the time-dependent biosensor were good within a statistically acceptable error range.